The National and Universal Significance of the 1821 Greek Revolution: The Perspective of Polish Romantic Philhellenes - Kalinowska, Maria (The Historical Review/La Revue Historique, 2022)
From the perspective of Polish Romantic poets such as Adam Mickiewicz, Juliusz Słowacki and Cyprian Norwid, the 1821 Greek Revolution was not merely a war for Greek freedom, but also had a more universal significance for other nations across Europe. In Polish poetic philhellenism, the uprising was seen as a great transnational war of common European values, a battle both for the freedom of individual nations as well for respect for every human being and the continuity of European culture.